Imaging the dynamics of transcription loops in living chromosomes - Morgan, Gary T. (Springer, 2018)
When in the lampbrush configuration chromosomes display thousands of visible DNA loops that are transcribed at exceptionally high rates by RNA polymerase II (pol II). These transcription loops provide unique opportunities to investigate not only the detailed architecture of pol II transcription sites but also the structural dynamics of chromosome looping, which is receiving fresh attention as the organizational principle underpinning the higher order structure of all chromosome states. The approach described here allows for extended imaging of individual transcription loops and transcription units under conditions in which loop RNA synthesis continues. In intact nuclei from lampbrush-stage Xenopus oocytes isolated under mineral oil, highly-specific targeting of fluorescent fusions of the RNA-binding protein CELF1 to nascent transcripts allowed functional transcription loops to be observed and their longevity assessed over time. Some individual loops remained extended and essentially static structures over time courses of up to an hour. However others were less stable and shrank markedly over periods of 30-60 minutes in a manner that suggested loop extension requires continued dense coverage with nascent transcripts. In stable loops and loop-derived structures the molecular dynamics of the visible nascent RNP component were addressed using photokinetic approaches. The results suggested that CELF1 exchanges freely between the accumulated nascent RNP and the surrounding nucleoplasm, and that it exits RNP with similar kinetics to its entrance. Overall it appears that on transcription loops nascent transcripts contribute to a dynamic self-organizing structure that exemplifies a phase-separated nuclear compartment.